Hati-Hati Intelijen Pemilu - Habibi, Andrian (UIN Syarif Hidayatullah Jakarta, 2019)
Abstract:The Ministry of Home Affairs Through the Director General of Politics and Public Administration conducts a series of activities to counteract any potential threats, obstacles, and disruptions to the implementation of General Elections in Indonesia. The expert team identified three electoral vulnerabilities in an area, namely: vulnerability to suffrage, the existence of disputes in the form of election objections adjudication, minority representation, public participation, candidate participation, election supervision, gender rights, campaigns, voter participation and voting. Therefore, Kominda is a form of prevention of the indication of vulnerability.Keywords: Kominda, Election, Ministry of Home Affairs Abstrak:Kementerian Dalam Negeri Melalui Dirjen Politik dan Pemerintahan Umum melakukan serangkaian kegiatan guna menangkal segala potensi ancaman, hambatan, dan gangguan terhadap terselenggaranya Pemilihan Umum di Indonesia. Tim ahli mengidentifikasi ada tiga kerawanan pemilu pada suatu daerah, yaitu: kerawanan hak pilih, adanya sengketa berupa ajudikasi keberatan pemilu, representasi minoritas, partisipasi publik, partisipasi kandidat, pengawasan pemilu, hak gender, kampanye, partisipasi pemilih dan pelaksanaan pemungutan suara. Oleh karena itu dilakukan Kominda sebagai bentuk pencegahan indikasi kerawanan tersebut.Kata Kunci: Kominda, Pemilu, Kemendagri